Change in land cover and water abstraction : modelling runoff effects in the Bot River Catchment - Stipinovich, Amalia (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Geography and Environmental Studies))--University of Stellenbosch, 2005.